1996
DOI: 10.1111/1523-1747.ep12340167
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases, Gelatinase and Collagenase, in Chronic Leg Ulcers

Abstract: Although extracellular proteolysis is a prerequisite for normal wound healing, uncontrolled proteolytic tissue destruction appears to be a pathogenic factor in non-healing wounds. The aim of our study was to compare the activities of the serine proteinases of polymorphonuclear origin, elastase and cathepsin G, and the metalloproteinases, gelatinase and collagenase, in chronic leg ulcer exudate (10 patients) and acute wound fluid (6 patients). Serine proteinase activities were low in leg ulcer exudates but very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 37 publications
10
187
0
3
Order By: Relevance
“…In chronic, non-healing wounds, these processes are disturbed and excessive tissue breakdown results in the failure to accumulate sufficient amounts of several key matrix components as a result of both decreased rates of protein biosynthesis 33 and greatly increased proteolytic activity. 34 Intriguingly, male gender is the primary factor predisposing to chronic wound healing states in humans, 23 and our recent studies have demonstrated that androgens impair healing in mouse and human models. 19 Previous studies have suggested that androgens may stimulate collagen production: DHT was shown to drive cutaneous expression of the gene encoding pro-a1 (I) collagen 35 and dermal collagen content was reported to be increased in elderly women receiving androgen treatment for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic, non-healing wounds, these processes are disturbed and excessive tissue breakdown results in the failure to accumulate sufficient amounts of several key matrix components as a result of both decreased rates of protein biosynthesis 33 and greatly increased proteolytic activity. 34 Intriguingly, male gender is the primary factor predisposing to chronic wound healing states in humans, 23 and our recent studies have demonstrated that androgens impair healing in mouse and human models. 19 Previous studies have suggested that androgens may stimulate collagen production: DHT was shown to drive cutaneous expression of the gene encoding pro-a1 (I) collagen 35 and dermal collagen content was reported to be increased in elderly women receiving androgen treatment for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors might be trapped within extracellular matrix molecules, 14 or degraded by increased protease activity found in chronic non-healing wounds. 15 Alternatively, growth factor production might be impaired at the gene expression level, as we have recently observed for VEGF in the genetically diabetic mouse. 16 Given these considerations, it stems evident that a reasonable approach to alter the microenvironment of the wounded tissue and to stimulate wound healing is the topical application of growth factors.…”
Section: Healing Is Concomitant With An Increase Of Production Of Andmentioning
confidence: 92%
“…As outlined above, a major pathogenic factor of the chronic non-healing wound environment is a high level of wound proteases (24)(25)(26)(27)29,30). Administration of recombinant TIMP-2, a metalloproteinase inhibitor, promoted tissue repair in a rat model (128).…”
Section: Candidate Genes For Tissue Repair: a Perspectivementioning
confidence: 99%
“…There is increasing evidence that the persisting infiltration of neutrophils and macrophages plays a major role in the generation of a protease rich and prooxidant hostile microenvironment (21)(22)(23). Recent experimental and several comprehensive clinical studies demonstrated that the proteolytic activity of matrix metalloproteinases and serine proteinases is significantly upregulated in the exudate of chronic wounds (24)(25)(26)(27), thus contributing to the degradation of extracellular matrix molecules (24,25), growth factors and their receptors (28)(29)(30). In addition, proteolytic degradation products generated by high protease activity in the chronic wound environment may exert inhibitory effects on cell function (31).…”
Section: Mechanisms Of Impaired Healingmentioning
confidence: 99%